KAJIAN PENERAPAN NILAI SIDDIQ, AMANAH, FATHANAH, DAN TABLIGH PADA KINERJA UMKM Di KECAMATAN MEDAN PERJUANGAN - Siti Mukti Intan Sari; Syamsul Effendi; Nurhudawi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the implementation of the values of siddiq, amanah, fathanah, and tabligh among Micro, Small, and Medium Enterprises (MSMEs) in Medan Perjuangan District, the obstacles faced in their implementation, and their impact on MSME performance. These values are the noble characteristics of Prophet Muhammad (PBUH) that serve as guidelines in Islamic business ethics and are important in building consumer trust and supporting business sustainability. However, in practice, some MSME actors have not fully implemented these values optimally.  This study employed a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation involving MSME actors in Medan Perjuangan District.  The results show that most MSME actors have implemented the values of siddiq, amanah, fathanah, and tabligh in their business activities. The value of siddiq is reflected in honesty when providing product information, amanah is demonstrated through responsibility in maintaining product quality and service, fathanah is shown through the ability to manage businesses and innovate, while tabligh is reflected in effective communication with consumers. The obstacles faced include limited knowledge, business competition, and the suboptimal use of technology. The implementation of these values has a positive impact on MSME performance, including increased consumer trust, improved service quality, customer loyalty, and business sustainability.